Impact of immobilization time on the recovery of ankle function after Achilles tendon rupture - Fernandes, Yasmim Vinhal; Gomes Filho, Jedson Vieira; Salazar, Vinicius Rafael Veiga; Simonassi Coutinho Sequim, Lorrainy (Journal of the Foot & Ankle, 2025)
Objective: To analyze the impact of immobilization time on the recovery of ankle function after Achilles tendon fracture. Methods: Studies published between 2013 and 2023, extracted from databases including PubMed, Scopus, Web of Science, Embase, and Cochrane Library, were included. Results: The analysis revealed that protocols with immobilization of 0-2 weeks resulted in better recovery of range of motion, muscle strength, and greater patient satisfaction, without a significant increase in complication rates or re-ruptures. In contrast, immobilization of 4-6 weeks was associated with greater joint stiffness and delayed return to sports activities. Conclusion: The findings reinforce the benefits of early mobilization after Achilles tendon rupture and reinforce the need for a more individualized approach. Level of Evidence I; Systematic Review